Oral Administration of 5-Aminolevulinic Acid Does Not Ameliorate Autoimmune Diabetes in NOD Mice - Shinpei Nishikido; Satoru Akazawa; Tetsuro Niri; Shin-Ichi Inoue; Katsuya Matsuda; Taiki Aoshi; Masahiro Nakashima; Ai Haraguchi; Ichiro Horie; Masakazu Kobayashi; Minoru Okita; Atsushi Kawakami; et al. (Diabetology, 2025)
Background/Objectives: 5-Aminolevulinic acid (5-ALA) is a biosynthetic precursor of heme that induces heme oxygenase-1 (HO-1). Therapeutic induction of HO-1 has shown effectiveness in various autoimmune disease models, including type 1 diabetes (T1D). However, the efficacy of 5-ALA as an HO-1 inducer in T1D models remains unexplored. This study aimed to investigate the therapeutic efficacy of oral 5-ALA administration in preventing autoimmune diabetes development in nonobese diabetic (NOD) mice. Methods: We evaluated diabetes incidence, levels of insulin autoantibody, and severity of insulitis in 5-ALA-treated and control NOD mice. HO-1 expression of dendritic cells in the pancreatic islets and spleen of 5-ALA-treated NOD mice was measured. The IFN-γ/IL-17 of islet-infiltrating T cells and IL-10/IL-12 productions of dendritic cells in the spleen of 5-ALA-treated NOD mice were assessed. We stimulated islet antigen-specific CD4+ T cells with islet antigen-pulsed dendritic cells in the presence of 5-ALA and examined the proliferation of the T cells. Finally, we adoptively transferred islet antigen-specific CD4+ T cells into 5-ALA-treated, immunodeficient NOD-Rag1 knockout mice, and diabetes incidence in recipients was determined. Results: Oral 5-ALA treatment did not significantly impact diabetes incidence, levels of insulin autoantibody, and insulitis. No significant difference was observed in HO-1 expression in dendritic cells and cytokine production of T cells and dendritic cells. Similarly, there was no significant difference in the proliferation of islet antigen-specific CD4+ T cells in vitro and diabetes induction in transfer experiments. Conclusions: Oral administration of 5-ALA has a limited effect on suppressing the development of autoimmune diabetes in NOD mice.